EVALUASI RAGAM METODE PERAWATAN LUKA PADA PASIEN DENGAN ULKUS DIABETES: LITERATURE REVIEW - Yusran Haskas; Ikhsan; Indah Restika (Universitas Prima Indonesia, 2021)
Diabetic ulcers are open sores on the skin surface due to complications of macroangiopathy. The global prevalence of diabetic ulcer complications varies from 3% in the Oceania region to 13% in Northern America, with a global average of 6.4%. Currently, the science of nursing is increasing. Evidence of developments in nursing is the development of various methods of treating diabetes ulcers, namely modern dressings, ozone therapy, and negative pressure wound therapy (NPWT). The aim of this study was to evaluate the currently more effective wound care methods for healing diabetic ulcers. This study used a systematic literature review design. Articles were collected through the PubMed and Google Scholar databases using the keywords diabetic ulcer, modern dressing, ozone therapy, negative pressure wound therapy (NPWT), and wound healing. The criteria for the articles used were original research, which the research design used was prospective, double-blind randomized comparative clinical trial, one group pre-test post-test, cross-sectional, single-blind randomized clinical trial, observational, experimental, retrospective were those published from 2016 to 2020. Researchers found 80,408 journals that match these keywords, then obtained 9 journals that match the inclusion criteria for review. The results of the literature review showed that NPWT was more effective in treating diabetic ulcers than modern dressings and ozone therapy. The conclusion is that negative pressure wound therapy (NPWT) is more effective because it is wounded heal faster, can minimize pain, and the length of stay in the hospital decreases.